Tomato short internodes and pedicels encode an LRR receptor-like serine/threonine-protein kinase ERECTA regulating stem elongation through modulating gibberellin metabolism - Zhao, Xueya; Zhang, Kunpeng; Zhang, Huidong; Bi, Mengxi; He, Yi; Cui, Yiqing; Tan, Changhua; Ma, Jian; Qi, Mingfang (Frontiers in Plant Science, 2023)
Plant height is an important agronomic trait. Dwarf varieties present several advantages, such as lodging resistance, increased yield, and suitability for mechanized harvesting, which are crucial for crop improvement. However, limited research is available on dwarf tomato varieties suitable for production. In this study, we report a novel short internode mutant named "short internode and pedicel (sip)" in tomato, which exhibits marked internode and pedicel shortening due to suppressed cell elongation. This mutant plant has a compact plant structure and compact inflorescence, and has been demonstrated to produce more fruits, resulting in a higher harvest index. Genetic analysis revealed that this phenotype is controlled by a single recessive gene, SlSIP. BSA analysis and KASP genotyping indicated that ERECTA (ER) is the possible candidate gene for SlSIP, which encodes a leucine-rich receptor-like kinase. Additionally, we obtained an ER functional loss mutant using the CRISPR/Cas9 gene-editing technology. The 401 st base A of ER is substituted with T in sip, resulting in a change in the 134 th amino acid from asparagine (N) to isoleucine (I). Molecular dynamics(MD) simulations showed that this mutation site is located in the extracellular LRR domain and alters nearby ionic bonds, leading to a change in the spatial structure of this site. Transcriptome analysis indicated that the genes that were differentially expressed between sip and wild-type (WT) plants were enriched in the gibberellin metabolic pathway. We found that GA 3 and GA 4 decreased in the sip mutant, and exogenous GA 3 restored the sip to the height of the WT plant. These findings reveal that SlSIP in tomatoes regulates stem elongation by regulating gibberellin metabolism. These results provide new insights into the mechanisms of tomato dwarfing and germplasm resources for breeding dwarfing tomatoes.